Acute Toxicity of Chlorpyrifos on the Freshwater Bivalves (Unio Tigridis) and Effects on Bioindicators (Baghdad Science Journal, 2024)
A freshwater bivalve plays a crucial function in aquatic habitats as the filtered water and burrowing mussels mix the sediment, thus increasing oxygen content and making the ecosystem healthier. The aim of the study is to see how chlorpyrifos affects biochemical markers in freshwater mussel Unio tigridis. About 180 individuals per taxon and water samples were collected from the Qandil water resource on the Greater Zab River, Erbil Province, Iraq. Once arrived at the lab, the individuals were kept in aquaria with river water and an air-conditioned room Temperature: 25±2 and Light: 12h/12h and acclimatized to laboratory conditions for seven days in aged tap water. The mussel's identification molecularly and the DNA sequence of the mussel includes U. tigridis supplied gene bank accession number ON872361, ON872362, ON872363, and ON872364 nucleotide sequencing. The 96-h toxicity of chlorpyrifos pesticide in the freshwater mussel U. tigridis was investigated using various nominal concentrations, including 50, 100, 200, 300 and 400 ppm. The water quality of the river and aquaria was tested for physicochemical parameters including water temperature, the potential of hydrogen ion pH, electrical conductivity EC, and total dissolved solids TDS, dissolved oxygen, total alkalinity, total hardness, calcium ion, magnesium ion. Water quality results of aquaria revealed that most tested variables were favorable for the breeding of mussels. The mortality of the mussels was observed daily and the 96 h LC50 value for mussels was 157.99 ppm. Within the tissue of the gills, Acetylcholinesterase (AChE), Glutathione S-transferase (GST), Catalase (CAT), and Malondialdehyde (MDA) were determined. The chlorpyrifos exposures caused significant increases in GST, CAT, and MDA. The elevation of oxidative stress biomarkers was inversely related to the AChE inhibition in the examined species. In conclusion water pollution by chlorpyrifos lead to unsafe condition for aquatic taxa.